Simulated ENSO's impact on tropical cyclone genesis over the western North Pacific in CMIP5 models and its changes under global warming. (3rd March 2019) - Tan, Kexin; Huang, Ping; Liu, Fei; Murakami, Hiroyuki; Hsu, Pang‐chi
Abstract : El Niño–Southern Oscillation (ENSO) plays an important role in modulating the location of tropical cyclone (TC) genesis over the western North Pacific (WNP). This study evaluated the simulation of the ENSO's impact on WNP TC genesis in 10 CMIP5 models based on a TC detection method, and projected its changes under global warming using the historical and the representative concentration pathway 8.5 (RCP8.5) simulations. The observed southeast–northwest shift role of ENSO in the WNP TC genesis location can be well reproduced in most of the models, although the strength of the ENSO's impact is underestimated as the underestimated climatological TC genesis frequency in these models. Moreover, we found the WNP TC during both El Niño and La Niña events shows an apparent eastwards shift under global warming. However, this eastwards shift of WNP TC genesis could be associated with the changes in climatological TC genesis but not the changes in the ENSO's impact. The projected changes in the ENSO's impact on WNP TC genesis is not as certain as we expected based on the previous conclusions of the robust changes in ENSO's impact on large‐scale environment. As a result, we suggest that both the TC genesis climatology and ENSO's impact on TC genesis simulated in the models need improvement in future to project the changes in ENSO's impact under global warming, and more models with 6‐hourly outputs used to detect TCs are needed to increase the confidence of multi‐model ensemble projections. Abstract : Based on the detected tropical cyclone (TC) activity, CMIP5 models can realistically reproduce the observed ENSO's impact on the western North Pacific (WNP) TC genesis, more TC genesis over the southeast WNP during El Niño events and more TC over the northwest during La Niña events. Under global warming, WNP TC during both El Niño and La Niña events shows an apparent eastwards shift. However, this eastwards shift of WNP TC genesis could be associated with the changes in climatological TC genesis but not the changes in the ENSO's impact.